Investigation of Food Poisoning Outbreak among Students in School A in Phuket - Sakulpat, Krit (Journal of Health Science of Thailand, 2017)
On June 18, 2009, social medicine unit of Vachira Phuket Hospital was informed by the emergency room that 15 students, from a same school, had food poisoning symptoms. The investigation was immediately conducted in a case-control study in order to identify the cause of and control this outbreak. Data was collected by direct interview methods. There were a total of 48 cases, all were students, which matched with defined food poisoning criteria. Attack rate among students was 5.6 percent. Fifth and sixth grade students who took Ultra - High Temperature milk had highest specific attack rate which were 31.9 and 9.1 percent respectively. Drinking Ultra - High Temperature milk with abnormal sour flavor taste and drinking Ultra - High Temperature milk with abnormal sediment- cottage-cheese like-showed statistical significant associations with food poisoning symptoms (odds ratios 15.07 and 14.58 respectively). It was found that the boxes of milk were stored in a room and piled up more than a maximum limit. Abnormal shape of and creases on milk boxes with abnormal sour flavor milk inside were observed. Staphylococcus aureus were found in one sample of vomit and one sample of left-over milk. Guideline of milk storage was implemented in all schools in Phuket in order to prevent this avoidable incidence in the future.